Черепахи неогеновых и антропогеновых отложений Украины Сообщение I. Семейство большеголовых черепах (Platvsternidae) - Таращук, В.И. (Вестник зоологии, 1971)
For the first time the fossil representative of the Platysternidae family (Macrucephalochelyss pontica, Tar , 1960) is described by the skull fragment from the Pontian limestones of the Odessa environs. Later on some more fossils belonging to the same species
were found in the territory of the Ukraine, including the first complete skull from the
Pontian deposits of the Crimea. Its full description is given in detail. A general review
of the findings of fossil turtles in the territory of the Ukraine is presentated and the history
of their study is elucidated.